The incidence of significant relationships between selected parameters of feet and parameters of trunk in adolescents aged 14-18 years - Mirosław Mrozkowiak; Mariusz Posłuszny; Marek Sokołowski; Alicja Kaiser (Kazimierz Wielki University, 2018)
Introduction. The analysis of correlations concerning 2,343 observations of more than 150 parameters of body posture revealed that the distribution of significant relationships in each of selected age and gender ranges was incidental and random, therefore it was impossible to prove any regularities or dependencies between the studied parameters. Material and method. The study conducted with the group of adolescents aged 14 to 18 years enabled to record 2,343 observations with regard to the measurement of the 90 parameters describing trunk and feet. The station for an assessment of body posture and feet using the photogrammetric method consisted of a computer, a card, software, a display monitor, a printer and a projection-reception device with a camera to measure selected parameters. Findings 1. The values of left foot parameters correlated significantly more with trunk parameters than right foot parameters. Particularly high correlations were observed in the following parameters: width and length of right foot and the surface of plantokonturogram (the plantar side of the feet). 2. Foot parameters revealed the most significant relationship with trunk parameters in the sagittal plane, then in the frontal plane to a lesser extent and sporadically in the transverse plane. Trunk parameters with which foot parameters correlated most often included: the angle of body bent to the left side in the frontal plane and height of lumbar lordosis, the inclination of the upper thoracic region, length of lumbar lordosis, height of thoracic kyphosis, asymmetry in height of scapulas with the right scapula up.